Evolution of pogo, a separate superfamily of IS630-Tc1-mariner transposons, revealing recurrent domestication events in vertebrates - Bo Gao; Yali Wang; Mohamed Diaby; Wencheng Zong; Dan Shen; Saisai Wang; Cai Chen; Xiaoyan Wang; Chengyi Song (Mobile DNA, 2020)
Abstracts Background Tc1/mariner and Zator, as two superfamilies of IS630-Tc1-mariner (ITm) group, have been well-defined. However, the molecular evolution and domestication of pogo transposons, once designated as an important family of the Tc1/mariner superfamily, are still poorly understood. Results Here, phylogenetic analysis show that pogo transposases, together with Tc1/mariner, DD34E/Gambol, and Zator transposases form four distinct monophyletic clades with high bootstrap supports (> = 74%), suggesting that they are separate superfamilies of ITm group. The pogo superfamily represents high diversity with six distinct families (Passer, Tigger, pogoR, Lemi, Mover, and Fot/Fot-like) and wide distribution with an expansion spanning across all the kingdoms of eukaryotes. It shows widespread occurrences in animals and fungi, but restricted taxonomic distribution in land plants. It has invaded almost all lineages of animals—even mammals—and has been domesticated repeatedly in vertebrates, with 12 genes, including centromere-associated protein B (CENPB), CENPB DNA-binding domain containing 1 (CENPBD1), Jrk helix–turn–helix protein (JRK), JRK like (JRKL), pogo transposable element derived with KRAB domain (POGK), and with ZNF domain (POGZ), and Tigger transposable element-derived 2 to 7 (TIGD2–7), deduced as originating from this superfamily. Two of them (JRKL and TIGD2) seem to have been co-domesticated, and the others represent independent domestication events. Four genes (TIGD3, TIGD4, TIGD5, and POGZ) tend to represent ancient domestications in vertebrates, while the others only emerge in mammals and seem to be domesticated recently. Significant structural variations including target site duplication (TSD) types and the DDE triad signatures (DD29–56D) were observed for pogo transposons. Most domesticated genes are derived from the complete transposase genes; but CENPB, POGK, and POGZ are chimeric genes fused with additional functional domains. Conclusions This is the first report to systematically reveal the evolutionary profiles of the pogo transposons, suggesting that pogo and Tc1/Mariner are two separate superfamilies of ITm group, and demonstrating the repeated domestications of pogo in vertebrates. These data indicate that pogo transposons have played important roles in shaping the genome and gene evolution of fungi and animals. This study expands our understanding of the diversity of pogo transposons and updates the classification of ITm group.